Distinct CD8 T Cell Populations with Differential Exhaustion Profiles Associate with Secondary Complications in Common Variable Immunodeficiency - Klocperk, Adam; Friedmann, David; Schlaak, Alexandra Emilia; Unger, Susanne; Parackova, Zuzana; Goldacker, Sigune; Sediva, Anna; Bengsch, Bertram; Warnatz, Klaus (Journal of clinical immunology, 2022)
PURPOSE: Common variable immunodeficiency (CVID) is the most frequent symptomatic primary immunodeficiency, with heterogeneous clinical presentation. Our goal was to analyze CD8 T cell homeostasis in patients with infection only CVID, compared to those additionally affected by dysregulatory and autoimmune phenomena. METHODS: We used flow and mass cytometry evaluation of peripheral blood of 40 patients with CVID and 17 healthy donors. RESULTS: CD8 T cells are skewed in patients with CVID, with loss of naïve and increase of effector memory stages, expansion of cell clusters with high functional exhaustion scores, and a highly activated population of cells with immunoregulatory features, producing IL-10. These findings correlate to clinically widely used B cell-based EURO classification. Features of exhaustion, including loss of CD127 and CD28, and expression of TIGIT and PD-1 in CD8 T cells are strongly associated with interstitial lung disease and autoimmune cytopenias, whereas CD8 T cell activation with elevated HLA-DR and CD38 expression predict non-infectious diarrhea. CONCLUSION: We demonstrate features of advanced differentiation, exhaustion, activation, and immunoregulatory capabilities within CD8 T cells of CVID patients. Assessment of CD8 T cell phenotype may allow risk assessment of CVID patients and provide new insights into CVID pathogenesis, including a better understanding of mechanisms underlying T cell exhaustion and regulation.
Keywords: běžná variabilní imunodeficience; Exhaustion; Common Variable Immunodeficiency; HLA-DR Antigens; T cells; antigeny CD279; antigeny CD28; interleukin-10; Programmed Cell Death 1 Receptor; CD28 Antigens; CVID; HLA-DR antigeny; CD8-pozitivní T-lymfocyty; Humans; Differentiation; Immunodeficiency; Interleukin-10; CD8-Positive T-Lymphocytes; lidé; Activation